Eliminating rabies in Tanzania? Local understandings and responses to mass dog vaccination in Kilombero and Ulanga districts. - Kevin Bardosh; Maganga Sambo; Lwitiko Sikana; Katie Hampson; Susan C Welburn (Public Library of Science (PLoS), 2014)
With increased global attention to neglected diseases, there has been a resurgence of interest in eliminating rabies from developing countries through mass dog vaccination. Tanzania recently embarked on an ambitious programme to repeatedly vaccinate dogs in 28 districts. To understand community perceptions and responses to this programme, we conducted an anthropological study exploring the relationships between dogs, society, geography and project implementation in the districts of Kilombero and Ulanga, Southern Tanzania.Over three months in 2012, we combined the use of focus groups, semi-structured interviews, a household questionnaire and a population-based survey. Willingness to participate in vaccination was mediated by fear of rabies, high medical treatment costs and the threat of dog culling, as well as broader notions of social responsibility. However, differences between town, rural and (agro-) pastoralist populations in livelihood patterns and dog ownership impacted coverage in ways that were not well incorporated into project planning. Coverage in six selected villages was estimated at 25%, well below official estimates. A variety of problems with campaign mobilisation, timing, the location of central points, equipment and staff, and project organisation created barriers to community compliance. Resource-limitations and institutional norms limited the ability for district staff to adapt implementation strategies.In the shadows of resource and institutional limitations in the veterinary sector in Africa, top-down interventions for neglected zoonotic diseases likes rabies need to more explicitly engage with project organisation, capacity and community participation. Greater attention to navigating local realities in planning and implementation is essential to ensuring that rabies, and other neglected diseases, are controlled sustainably.